Exploring ESP Learners’ Self-Regulation in Online Learning Environment - Siti Kustini (Universitas Cokroaminoto Palopo, 2022)
This study attempts to find out the learner’s level of self-regulation in ESP online learning program during the period of Covid-19 pandemic. Self-regulation is concerned with the ability of learners to manage their own learning which subsequently yields positive impacts on their learning results. Learners make personal initiative, employ effective strategies to achieve personally meaningful learning objectives, and closely monitor their understanding to identify and eliminate any of comprehensible issues. This study applied explanatory sequential mixed approaches in which quantitative research was conducted prior to qualitative. The quantitative research was employed to collect general data and to obtain a picture of learners’ self-regulation. To this end, Online Self-Regulated Learning Questionnaire (QSLQ) was utilized. The QLSQ contained six subscale elements including: environment setting; goal planning; time management; assistance seeking; task strategies; and self-evaluation. The survey was composed of 24 Likert-type scales to measure student’s ability to self-regulate their learning in online delivery format. The qualitative data was conducted through interviews to help explain and explore the phenomenon deeper. The interview question protocols for the interviews covered among others motivation in online learning, self-regulation strategies, and environment setting. The participants of the study were 147 ESP students of Informatics Engineering Study Program at a state polytechnic in Banjarmasin. The findings from quantitative data indicate that the students had a high level of setting goals in their learning, high awareness in environment structuring, good level of task strategies, high ability in time management, high awareness of help seeking and self-evaluation. The data from the interviews reveal that the students’ motivation remained constant during the pandemic, their confidence in learning increased, their learning strategies changed, and their learning environment also changed. This study hopefully will be useful for ESP educators and other policy makers in designing the instructional process in an ESP online setting.